Structural and thermal analysis of integrated thermal protection systems with C/SiC composite cellular core sandwich panels. (25th February 2018) - Wei, Kai; Wang, Kaiyu; Cheng, Xiangmeng; Peng, Yong; Li, Maojun; Yang, Xujing
Highlights: The devised ITPS integrates light weight and high service temperature up to 1600 °C. The critical relative density of the failure models in the ITPS is identified. The effective thermal conductivity of the ITPS is derived and numerical verified. Preliminary sizing analysis identifies the acceptable dimensions of the ITPS. The ITPS incorporates much low areal density ρ a and high effective specific heat C eff . Abstract: Current studies of the integrated thermal protection system (ITPS) are mainly focused on the metal corrugated core sandwich panels, resulting in low service temperature and high weight level. Here, by contrast, ITPS based on lightweight C/SiC composite sandwich panels with corrugated, pyramid as well modified pyramid cores are proposed for purpose of raising the service temperature, and lowering the weight level. As the basis, the structural analysis identifies the critical relative density of the failure models in the proposed ITPS, giving a guide to avoid the buckling failure. The effective thermal conductivity, which characterized the ability of heat conduction, is theoretically derived and numerical verified. Moreover, under typical aerodynamic heat and pressure, preliminary sizing analysis figures out the accepted dimensions of the ITPS with the fulfillment of both thermal and mechanical constraints. A new evaluate index: effective specific heat C eff is proposed to compare the ITPS quantitatively and objectively. The comparison firmly confirms that the areal densities of the ITPSs with the proposed C/SiC pyramid and modified pyramid sandwich panels are much lower than those of the reported ITPSs with metal corrugated core sandwich panels. Meanwhile, the effective specific heat of the proposed ITPS is much higher than that of the reported ITPSs, revealing that the proposed ITPS incorporates the advantages of lower areal density and higher service temperature up to 1600 °C compared with the reported metal corrugated core ITPS.